NiFe2O4 nanospheres with size-tunable magnetic and electrochemical properties for superior supercapacitor electrode performance. (10th December 2021) - Arun, Thirumurugan; Kavinkumar, T.; Udayabhaskar, R.; Kiruthiga, R.; Morel, Mauricio J.; Aepuru, Radhamanohar; Dineshbabu, N.; Ravichandran, K.; Akbari-Fakhrabadi, Ali; Mangalaraja, R.V.
Highlights: Ferric ions induced size reduction of NiFe2 O4 nanospheres. Size depended variation in saturation magnetization from 45 to 29 emu/g. Fabrication and performance analysis of asymmetric solid-state cell. Electrode exhibited a higher energy density of 22.5 Wh/ Kg. Cyclic stability of the cell showed capacity retention of 126 %. Abstract: Hereby, we present our efforts to understand the influence of ferric ions in the preparation of NiFe2 O4 magnetic nanoparticles (MNPs) by facile chemical oxidation method. The variation in the Ferric ions content provoked size tunability of the MNPs (particle size reduced with increasing ferric ions content). The effect of ferric ions content on the prepared MNPs were analyzed for phase, morphological and magnetic characteristics by using X-ray diffraction (XRD), Field Emission Scanning Electron Microscopy (FESEM), Vibrating Sample Magnetometer (VSM) and Thermomagnetic Analysis (TMA) measurements. The saturation magnetization and coercivity values were observed to be 45 emu/g and 90 Oe for the nanoparticles prepared without ferric ions. The size depended reduction in magnetization and coercivity values were evident for increased ferric ion concentration. The curie transition temperature was observed to be 584 °C from TMA analysis. The cyclic voltammogram, galvanostatic charge/discharge and electrochemical impedance measurements were carried out to evaluate the electrochemical characteristics of prepared NiFe2 O4 nanoparticles for supercapacitor application. The highest specific capacitance of 277 F/g was observed for the NiFe2 O4 nanoparticles that prepared with 50 % of ferric ions (NF50). From the cyclic stability study, 101 % of capacitance retention was demonstrated up to 5000 cycles. An asymmetric two-electrode cell that fabricated with NF50 exhibited a maximum specific capacitance of 56 F/g (with an applied current density of 1 A/g) and higher energy density of 22.5 Wh/ Kg (with a power density of 0.85 kW/Kg). The cyclic stability study of the cell revealed the increased capacity retention (126 % up to 5000 cycles) due to the particle size reduction. The observed enhancements in the magnetic and electrochemical properties with the size reduction are discussed in-detail. The facile strategy presented by this work would give insights for high-performance supercapacitor electrode material. Graphical abstract: Image, graphical abstract